2010
DOI: 10.1128/jvi.00326-10
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MIP-1α (CCL3) by a Recombinant Rabies Virus Enhances Its Immunogenicity by Inducing Innate Immunity and Recruiting Dendritic Cells and B Cells

Abstract: ). In the present study, the immunogenicity of recombinant RABV expressing MIP-1␣ (rHEP-MIP1␣) was determined. It was found that intramuscular immunization of BALB/c mice with rHEP-MIP1␣ resulted in a higher level of expression of MIP-1␣ at the site of inoculation, increased recruitment of dendritic cells (DCs) and mature B cells into the draining lymph nodes and the peripheral blood, and higher virus-neutralizing antibody titers than immunization with the parent rHEP and recombinant RABVs expressing RANTES (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
73
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 34 publications
5
73
1
Order By: Relevance
“…Each qRT-PCR was carried out in duplicate with approximately 1 g of DNase-treated RNA and 10 nM primer pair solutions using a one-step SYBR green qRT-PCR mix kit (Toyobo). For the absolute quantification of viral genomic RNA (vRNA), a plasmid expressing the RABV N protein was used as a standard (12). For the relative quantification of CXCL13 or CXCR5, mRNA copy numbers were normalized to those of the housekeeping gene ␤-actin.…”
Section: Methodsmentioning
confidence: 99%
“…Each qRT-PCR was carried out in duplicate with approximately 1 g of DNase-treated RNA and 10 nM primer pair solutions using a one-step SYBR green qRT-PCR mix kit (Toyobo). For the absolute quantification of viral genomic RNA (vRNA), a plasmid expressing the RABV N protein was used as a standard (12). For the relative quantification of CXCL13 or CXCR5, mRNA copy numbers were normalized to those of the housekeeping gene ␤-actin.…”
Section: Methodsmentioning
confidence: 99%
“…The inability of wild-type (wt) RABV to induce VNA responses also has been reported in other animal species, such as mice (10), dogs (11), and skunks (12). On the other hand, experimental infection with laboratory-attenuated RABV induces VNA responses in laboratory animals (10,(13)(14)(15)(16)(17). Although the mechanism(s) by which different RABVs induce different VNA responses are unknown, recent studies (18-21) indicate that laboratory-attenuated RABV activates, while wt RABV evades, the host innate immune responses, particularly interferon (IFN) and chemokines, in the central nervous system (CNS).…”
mentioning
confidence: 99%
“…On the other hand, experimental infection with laboratory-attenuated RABV induces VNA responses in laboratory animals (10,(13)(14)(15)(16)(17). Although the mechanism(s) by which different RABVs induce different VNA responses are unknown, recent studies (18-21) indicate that laboratory-attenuated RABV activates, while wt RABV evades, the host innate immune responses, particularly interferon (IFN) and chemokines, in the central nervous system (CNS).Innate immune genes, such as chemokines, have been cloned into RABV vectors to enhance the immune responses (10,14,15,22). It was found that the overexpression of these innate immune genes stimulated higher levels of VNA production and provided better protection by activating more dendritic cells (DCs) than the parental virus (10, 15) (14,17).…”
mentioning
confidence: 99%
“…Since the recent introduction of "reverse genetics" technology (12,13), new live attenuated RABV can be designed, for instance, by gene mutations (see reference 14), duplication or triplication of the RabG gene (15,16), or simultaneous expression of inserted cytokine genes to stimulate the innate immune response (17,18). Some of them are promising candidates of rabies vaccines due to their apathogenicity and improved immunogenicity in animal models.…”
mentioning
confidence: 99%